Effect of Hole Extraction from the Base Region of a Silicon p–n–p Transistor on its Reactive Impedance - N. I. Gorbachuk; N. A. Poklonski; Ya. N. Marochkina; S. V. Shpakovski (Приборы и методы измерений)
Transistor structures are the basic elements of integrated circuitry and are often used to create not only transistors themselves, but also diodes, resistors, and capacitors. Determining the mechanism of the occurrence of inductive type impedance in semiconductor structures is an urgent task, the solution of which will create the prerequisites for the development of solid-state analogs of inductors. The purpose of the work is to establish the effect of extraction of non-equilibrium charge carriers from the base region on the reactive impedance of a bipolar p–n–p transistor.Using impedance spectroscopy in the frequency range 20 Hz–30 MHz, the structures based on p–n–p transistors KT814G manufactured by JSC “INTEGRAL” were studied. It is shown that in the transistor structures it is possible to observe the “effect of negative capacitance” (inductive type impedance). It is established that the most probable cause of the inductive type impedance is the accumulation of uncompensated charge of holes in the base, the value of inductive impedance is influenced by both the injection efficiency in the base–emitter junction and the extraction efficiency in the base–collector junction.The results can be applied in the elaboration of technologies for the formation of elements of silicon based integrated circuits with an impedance of inductive type.